Engineering Geology for Society and Territory - Volume 3 2014
DOI: 10.1007/978-3-319-09054-2_113
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Recharge of Fractured Aquifers: A Case Study in a Flysch Rock Mass of the Northern Apennines (Italy)

Abstract: 12 springs from the northern Apennines of Italy were studied by means of a comprehensive hydrogeological investigation to unravel recharge processes taking place in a highly fractured slab of flysch rock hosting the corresponding aquifers. Several campaigns were carried out during the period 2005–2008 to gather springs’ discharge together with electrical conductivity and temperature data. Water samples were collected and allowed the determination of the major ions (Ca2+, Mg2+, Na+, K+, SO4 2−, HCO3 −, Cl−) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 3 publications
2
22
0
Order By: Relevance
“…This value is in the range of those found in other fractured flysch slabs in the northern Apennines (Corsini et al 2009, Cervi et al 2014 and allows for the quite fast depletion of the aquifer (QTOT from 220 Ls -1 to about 28 Ls -1 in 6 months). If no recharge had been supplied to the system at the beginning of autumn, the aquifer would have been completely emptied within 11 months.…”
Section: Resultssupporting
confidence: 52%
“…This value is in the range of those found in other fractured flysch slabs in the northern Apennines (Corsini et al 2009, Cervi et al 2014 and allows for the quite fast depletion of the aquifer (QTOT from 220 Ls -1 to about 28 Ls -1 in 6 months). If no recharge had been supplied to the system at the beginning of autumn, the aquifer would have been completely emptied within 11 months.…”
Section: Resultssupporting
confidence: 52%
“…Doveri, M. et al utilized water isotopes as environmental tracers for the conceptual understanding of groundwater flow [6]. Cervi, F. et al studied 12 springs from the northern Apennines of Italy by means of a comprehensive hydrogeological investigation to unravel recharge processes taking place in a highly fractured slab of flysch rock hosting the corresponding aquifers [7]. At present, the development of a groundwater recharge model and a sensitivity analysis of groundwater to climate change are still in the research and exploration stages in China [8].…”
Section: Introductionmentioning
confidence: 99%
“…The numerical simulations demonstrated that the deformation was driven by stress reduction in the tuff plate. Moreover, the evolution of the phenomenon can be also related to the presence of a well-developed system of fractures within the rock mass , which can result in a higher secondary permeability (Cervi et al 2014). Due to the almost-impermeable clay-rich substratum, an aquifer can develop inside the rock mass and eventually play an important role in the stability of the slopes .…”
Section: Introductionmentioning
confidence: 99%